Context and development of the theme of city in lyrics of Bratislava rock groups - Zemanova, Zuzana (Bohemica Olomucensia, 2013)
The paper deals with the projection of space of city in several lyrics, which have been realized by Bratislava rock groups and singers since the end of 1960s, especially in 1970s and 1980s. It follows their characteristic features, development and modifications. The analysis is based on the background of popular music in Slovakia in general and on the context of cultural politics as well. It is also connected to the historical and architectural transformation of Bratislava after the World War II.